2022
DOI: 10.1371/journal.pone.0258673
|View full text |Cite
|
Sign up to set email alerts
|

Gender effect in survival after out-of-hospital cardiac arrest: A nationwide, population-based, case-control propensity score matched study based Korean national cardiac arrest registry

Abstract: Objective This study aimed to describe the relationship between sex and survival of patients with out-of-hospital cardiac arrest (OHCA) and further investigate the potential impact of female reproductive hormones on survival outcomes, by stratifying the patients into two age groups. Methods This retrospective, national population-based observational, case-control study, included Korean OHCA data from January 1, 2009, to December 31, 2016. We used multiple logistic regression with propensity score-matched dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Another possibility is that the protective effect of estrogen is present for only a brief period after a stressful event. Choi et al [ 24 ] assessed differences in survival among male and female patients after OHCA and concluded that women in the reproductive age group had a better chance of survival than men. Their conclusion is consistent with the findings of Deitch et al [ 20 ] and McKinley et al [ 21 ], who speculated that the initial protective effect of elevated estrogen decreased with time from the initial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that the protective effect of estrogen is present for only a brief period after a stressful event. Choi et al [ 24 ] assessed differences in survival among male and female patients after OHCA and concluded that women in the reproductive age group had a better chance of survival than men. Their conclusion is consistent with the findings of Deitch et al [ 20 ] and McKinley et al [ 21 ], who speculated that the initial protective effect of elevated estrogen decreased with time from the initial injury.…”
Section: Discussionmentioning
confidence: 99%
“…All p-values were two-sided, and a p-value < 0.05 was considered significant. All Springer et al 10.3389/fcvm.2023.1265978 calculations were performed using the statistical analysis software R (R Core Team, 2023).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Studies have suggested that women exhibit overall lower survival rates and worse neurological outcomes after conventional CPR for CA compared with men (7)(8)(9). When analysing women of reproductive age, these effects seem to be suspended, with favourable outcomes reported in this collective (10). Whether these gender differences exist in the context of eCPR remains widely unknown, with only limited data available reporting inconsistent results (11,12).…”
Section: Introductionmentioning
confidence: 97%